ACCESS AND OWNERSHIP: EXPLORING MUSIC CONSUMERS’ PERCEPTION OF DIGITAL MUSIC PRODUCT BASED ON PERCEIVED RISKS – A CORRESPONDENCE ANALYSIS - Tulandi, Wandy M.G.; Worang, Frederik G.; Pandowo, Merinda Ch. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The purpose of this research is to explore the perception of music consumers regarding digital music product based on the perceived risks related to it. This study uses an exploratory research design to explore the topic of music consumers’ perception of digital music product in Manado City based on perceived risk. This research will use Correspondence Analysis - Perceptual mapping as the tool for the data analysis. Based on the data gathered from 150 music consumers in Manado, the researcher found that music consumers has a relatively high perception of risk towards two types of digital music product which are Legal Download and Illegal Download. While Music Streaming on other hand has a very low degree of risk perception on all three types of perceived risk. For the music content creators it should be noted that today’s music listeners has started to embrace the new trend of streaming service. Therefore content creator should consider utilizing this new platform instead of relying too much on conventional ownership such as downloads.